Youth entrepreneurship and business growth: A study from youth entrepreneurs in Malaysia - Ellvina Stephen; Nik Nur Dayana Sahira Nik Kamarul Anuar; Nurain Afiqah Rizal; Zakia Muthia (2023)
In Malaysia, SMEs are developing, but exposure to youth entrepreneurs is still lacking in any study. Researchers feel that a good knowledge of youth entrepreneurs can encourage the government to implement various effective programs or strategies that have an impact in terms of social and economic growth of the country. This study aims to examine the key drivers that support youth entrepreneurship and business growth in Malaysia in terms of social network, digital knowledge, and business experience. A quantitative method is used in completing this research while a simple random sampling is used to collect data. Findings from the study revealed that 189 female youth and 69 male youth in Malaysia have exposure to the growth of youth entrepreneurs in starting a business. The use of SPSS to analyze the data shows the independent variable results, namely social network and digital knowledge have a significant relationship with the growth of youth start-up in Malaysia. Limitations and recommendations of this study also included, which is to enable researchers in the future to collect more data and produce more significant results.